2008
DOI: 10.1093/jnci/djn325
|View full text |Cite
|
Sign up to set email alerts
|

A Central Role for Tumor-derived Monocyte Chemoattractant Protein-1 in Malignant Pleural Effusion

Abstract: MCP-1 produced by tumor cells is an important determinant of their capacity to induce the formation of MPE and may be a useful target for the treatment of malignant pleural disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
131
0
28

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(172 citation statements)
references
References 38 publications
13
131
0
28
Order By: Relevance
“…It is known that MCP-1 secreted from tumor cells is an important determinant in the pathogenesis of human lung cancers. Previous studies have also demonstrated that blockade of MCP-1, as mediated by neutralizing antibodies, in several animal models of non-small cell lung cancer significantly slowed the growth of primary tumors (37,38). These results, thus, supported the notion that FMS could not only suppress the LLC1 cell growth but also attenuate relative inflammation levels in vivo.…”
Section: Fuc-enriched F3 Polysaccharide Fraction Induced Antibodies Rsupporting
confidence: 64%
“…It is known that MCP-1 secreted from tumor cells is an important determinant in the pathogenesis of human lung cancers. Previous studies have also demonstrated that blockade of MCP-1, as mediated by neutralizing antibodies, in several animal models of non-small cell lung cancer significantly slowed the growth of primary tumors (37,38). These results, thus, supported the notion that FMS could not only suppress the LLC1 cell growth but also attenuate relative inflammation levels in vivo.…”
Section: Fuc-enriched F3 Polysaccharide Fraction Induced Antibodies Rsupporting
confidence: 64%
“…For the first time, murine osteopontin functions during in vivo metastasis are linked with CCL2 signaling, a known druggable trait of thoracic tumor dissemination. [47][48][49][50] CCL2 can, in turn, enhance osteopontin signaling, since it augments the expression of the osteopontin receptor a v b 3 integrin. 51,52 Both molecules activate pathways such as FAK/Akt, MAPK, JAK2-Stat5, p38MAPK, and NF-kB in endothelial cells, thereby promoting adhesion, extravasation, and immune evasion of circulating tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of protein and lactate dehydrogenase (LDH) in MPE is a prognostically significant biochemical feature (8). In addition, numerous types of cytokine, including interleukin (IL)-1β, IL-5, IL-6, IL-8, IL-10, IL-12, monocyte chemoattractant protein-1 (MCP-1) and tumor necrosis factor-α (TNF-α) are detected in MPE (9)(10)(11)). An increased concentration of vascular endothelial growth factor (VEGF), which is mainly secreted from endothelial cells is also detected in MPE (12).…”
Section: Introductionmentioning
confidence: 99%
“…Since clinical features, biomedical features and numerous cytokines have been reported to be associated with MPE, and a single parameter may not serve as an optimal biomarker for predicting MPE (8)(9)(10)(11)(12)(13)(14)(15), the present study assessed whether a combination of biochemical features, clinical features and cytokine levels in pleural effusion may distinguish between BPE and MPE. The clinical and biochemical features of pleural effusion were determined and the concentration of cytokines in collected BPE and MPE samples was evaluated using cytometric bead arrays.…”
Section: Introductionmentioning
confidence: 99%